The Impact of Educational Laws and Policies on National Development in Nigeria: Challenges and Pathways for Effective Implementation - Berebon, Charles (dialektika kontemporer, 2024)
Education is universally recognized as a fundamental human right and serves as a cornerstone for social justice and societal advancement. It is one of the most powerful tools for fostering positive change and represents one of the best investments any nation can make to drive economic, political, social, and human development (Mandela, 2000). Education empowers individuals, equips them with the skills needed to participate fully in society, and lays the groundwork for sustainable national progress. In Nigeria, the philosophy of education is rooted in transforming individuals into responsible, effective citizens by ensuring equal educational opportunities for all, regardless of background or socioeconomic status. This vision is enshrined in the National Policy on Education (2014), which emphasizes the importance of providing functional and accessible education to every Nigerian, regardless of state of origin, religion, family socioeconomic status, or geographic location. The policy reflects Nigeria's commitment to building an inclusive and productive society through education that equips individuals with the skills and knowledge required to thrive. The development of a nation is intrinsically linked to the effectiveness of its educational laws and policies. In recognition of this, governments worldwide have made educational policies a priority, viewing them as critical tools for national development. In Nigeria, the role of education policies in fostering national development cannot be overstated; however, despite the significant emphasis on policy development, numerous challenges hinder their effective implementation. These obstacles have stifled the full realization of the transformative potential of education and have contributed to ongoing difficulties in achieving academic excellence across the nation. This paper explores the fundamental concepts of educational laws and policies, offering a concise history of their development within Nigeria. It also examines the philosophical foundations of educational policies and the complexities involved in adapting them to Nigeria's unique sociopolitical and cultural landscape. By analyzing these challenges and revisiting the philosophical principles behind Nigeria's educational policies, this discussion seeks to provide insights into how educational reforms can be more effectively implemented to foster genuine social progress and contribute to national development.